PERPUTARAN PIUTANG PADA PT.INTRACOPENTA,Tbk - Simbolon, Nora Yuniati (EKONOMIA, 2015)
Nora Yuniati Simbolon, 2014, Faculty og Economics, University of August 17, 1945 samarinda in East Kalimantan, Accounts Receivable Turnover Analysis on PT.Intracopenta,Tbk. Under the guidance of Mr.Prof.Dr.LCA.Robin Jonathan, MM., M.Si and Mrs.Dr.Dra.Ec. Elfreda Alponia Lau, M.Si               Outlines the basic theory of Accounting, Financial Accounting, the concept of internal control and internal control concepts, hypotheses and conceptual definitions. Increased accounts receivable each year due to policy taken by the company is to provide credit facilities to its customers, to increase the number of sales and the amount of receivables not yet collected at the time in which the debtor does not pay off the debt at maturity that has been set by the company. It can be seen from the accounts receivable turnover rate has decreased every year, and even to exceed the limits established credit payment by the company.